Giant magnetic moment in epitaxial Fe3O4 thin films on MgO (100) - SHVETS, IGOR; ARORA, SUNIL; WU, HAN-CHUN (My University, 2008)
Magnetization studies on well characterized epitaxial magnetite (Fe3O4) thin films grown on MgO(100) show that the ultrathin films (<5?nm thickness) are ferromagnetic and their magnetic moments are much greater than those of bulk magnetite, particularly at a thickness of 20 nm or below. The observation of a ferromagnetic nature in ultrathin magnetite films (<5?nm) is in contrast to the previously accepted dead layer interface model or a superparamagnetic behavior for ultrathin films of magnetite. From detailed spin-polarized density functional theory based calculations of Fe3O4-MgO interface, we calculate a deviation in spin moment of the Fe atoms in the vicinity of the interface from their bulk values, which is insufficient to explain the observed results. Orbital moment contribution for the surface Fe atoms was found to be quite small. The noncompensation of spin moments between the tetrahedral (A) and octahedral (B) sublattices at the surface and antiphase-domain boundaries are inferred to be the main factor contributing to the observed enhanced magnetic moment.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; thin films